The value of concomitant testing of cutaneous silent period with sympathetic skin response and heart rate variability in Type-2 diabetes patients: An electrophysiological study - Aya Falah Alrekabi; Safaa Hussein. Alshemmari (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the association among cutaneous silent period, sympathetic skin response and heart rate variability in diabetes patients. Method: The case-control study was conducted at the Department of Physiology, College of Medicine, Al-Mustansiriyah University, Baghdad, Iraq, from November 1, 2020, to May 20, 2021, and comprised 24 healthy controls in Group I and 49 patients of type 2 diabetes in Group II who were recruited from the neuro-electrophysiological unit of Al-Imamain Al-Kadhmean Teaching Hospital, Baghdad, Iraq. Both groups were subjected to cutaneous silent period, sympathetic skin response and heart rate variability testing. Data was analysed using SPSS 24. Results: Of the 73 subjects, 24(32.9%) were in Group I and 49(67.1%) were in Group II. Cutaneous silent period mean latency values were significantly increased in Group II compared to Group I (p<0.05), and a negative sympathetic skin response in the right lower limb was significantly different between the groups (p<0.001). There was no significant correlation between Cutaneous silent period and sympathetic skin response values (p>0.05). Heart rate variability was significantly increased in diabetic patients with negative sympathetic skin response compared to those with positive sympathetic skin response (p<0.05). Conclusion: Simultaneous measurement of cutaneous silent period, sympathetic skin response and heart rate variability should be done as there were no strong correlation among the tests in diabetic patients. Key Words: Diabetes, Heart, Extremity,